Technical knowledge of health professionals regarding the management of syphilis and its relationship with Permanent Health Education (Research, Society and Development, 2021)
Objective: To map the technical knowledge of health professionals regarding the management of syphilis and its relationship with Permanent Education in Health. Methodology: An integrative review study, carried out in the period of November 2020. 793 publications were found, 459 on the Portal VHL and 334 on the CAPES Journal Portal. The final sample consisted of 10 articles, being 08 articles from the VHL Portal and 02 articles from the CAPES Periodical Portal. Results: The methodological approach was entirely quantitative in terms of congenital syphilis and syphilis in pregnancy, with 3 international and 7 national studies. Knowledge gaps were found such as the definition of cases of congenital syphilis, the use of serological tests and the choice of antibiotic alternatives for the treatment of pregnant women allergic to penicillin. Only two studies used technological tools for permanent education and demonstrated a positive effect in increasing the knowledge of health professionals. Conclusion: It is necessary to publish more studies that evaluate knowledge and the production of Permanent Education in Health tools to improve the quality of syphilis management.